1987
DOI: 10.1524/zpch.1987.154.part_1_2.091
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Photochromic Effect of Spiro [indolino-naphthoxazine] Derivatives by Time-Resolved Spectroscopy

Abstract: Based on the results of different spectroscopic techniques, a reaction scheme is proposed to explain the photochromism of indolinospironaphthoxazine derivatives. Pump-probe experiments with picosecond time-resolution show that bond breakage in the excited spiro form occurs within less than 2 ps. The primary photoproduct, a non-planar intermediate X*, decays into a mixture of isomers, usually termed "photomerocyanines". The lifetime of the intermediate X*, which varies between 3 and 11 ps, depends both on natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In-depth basic research on the photophysics and photochemical processes of spirooxazines has been carried out. Schneider et al studied the mechanism of photochromism of spirooxazines by picosecond time-resolved absorption spectra, as well as time-resolved spontaneous and coherent anti-stokes Raman scattering [ 40 ]. Kellmann and colleagues studied the light physics and dynamics of spirooxazines in 1989 [ 41 ].…”
Section: Structure and Mechanism Of Photochromismmentioning
confidence: 99%
“…In-depth basic research on the photophysics and photochemical processes of spirooxazines has been carried out. Schneider et al studied the mechanism of photochromism of spirooxazines by picosecond time-resolved absorption spectra, as well as time-resolved spontaneous and coherent anti-stokes Raman scattering [ 40 ]. Kellmann and colleagues studied the light physics and dynamics of spirooxazines in 1989 [ 41 ].…”
Section: Structure and Mechanism Of Photochromismmentioning
confidence: 99%
“…It has attracted much attention because of the wide variety of practical applications of photochromic systems most of which are spiro-compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Among them, the compounds of the spiroindolinonaphthooxazine series (SO) are a topic of increasing interest because of their good colouring power and photofatigue resistance both providing a potential application in many new technologies such as data recording and storage, optical switching, displays and nonlinear optics (3-18).…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectrums were broad in both hydrogels; this was mainly related to the coloring mechanism. After UV illumination, bond breakage in the excited spiro form on SPO occurred; the intermediate X was produced first, which then decayed into zwitterionic merocyanines, because the merocyanines were mixture of at least four isomers and their optical spectrums were broad absorption bands [32]. We observed that UV irradiation of the hydrogel made by immersing method at 365 nm led to the maximum absorbance ( max ) at 620 nm (Figure 4(a)), while in the hydrogel made by polymerization method there was a shift in max to a shorter wavelength, which was 610 nm (Figure 4(b)).…”
Section: Photochromic Performance and Thermal Fading Kineticsmentioning
confidence: 99%